2006
DOI: 10.1016/j.foodchem.2005.01.001
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of carboxypeptidase B from pyloric ceca of the starfish Asterina pectinifera

Abstract: Carboxypeptidase B was purified from the pyloric ceca of the starfish Asterina pectinifera. The final enzyme preparation was nearly homogeneous in sodium dodecyl sulfate-polyacrylamide gel electrophoresis and its molecular weight was estimated as approximately 34,000. The value of the specificity constant (kcat/Km) for hydrolysis of benzoyl-glycyl-L-arginine by the purified enzyme was 1.72×10 5 M -1 sec -1 . The optimal pH and the optimal temperature of the enzyme were pH 7.5 and 55 ℃, respectively. The enzyme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 35 publications
1
12
0
Order By: Relevance
“…The procedure applied in the purification of CPB from zebra blenny is more efficient than that applied in the purification of CPB from ostrich S. camelus (Bradley et al, 1996) which yielded 3.4% after two steps of purification. However, it was similar to that applied in the purification of CPB from camel (Al-Ajlan and Bailey, 1999) and starfish Asterina pectinifera (Kishimura et al, 2006), which yielded 29.3 and 23% after four and three steps of purification, respectively. The purified enzyme gave a single band on SDS-PAGE, and its molecular weight was estimated to be 34.5 kDa (Figure 2), corresponding to that determined by gel filtration.…”
Section: Cpb Purificationsupporting
confidence: 67%
See 2 more Smart Citations
“…The procedure applied in the purification of CPB from zebra blenny is more efficient than that applied in the purification of CPB from ostrich S. camelus (Bradley et al, 1996) which yielded 3.4% after two steps of purification. However, it was similar to that applied in the purification of CPB from camel (Al-Ajlan and Bailey, 1999) and starfish Asterina pectinifera (Kishimura et al, 2006), which yielded 29.3 and 23% after four and three steps of purification, respectively. The purified enzyme gave a single band on SDS-PAGE, and its molecular weight was estimated to be 34.5 kDa (Figure 2), corresponding to that determined by gel filtration.…”
Section: Cpb Purificationsupporting
confidence: 67%
“…The enzyme is highly stable over a broad pH range, maintaining over 100% of its original activity between pH 6.0 and 10.0, after incubation for 30 min at 25 • C, and more than 95 and 85% of its activity was retained at pH 6.0 and 11.0, respectively. The pH stability profile of S. basilisca CPB was similar to those of the starfish A. pectinifera (Kishimura et al, 2006) and A. amurensis (Kishimura and Hayashi, 2002).…”
Section: Effect Of Ph On Activity and Stability Of The Cpbmentioning
confidence: 56%
See 1 more Smart Citation
“…However, in the presence of CoCl 2 at 1 mM, APE activity became stabilized, with 1.0 and 1.2 U/mg protein at 60 and 80°C, respectively (Figure 4b). Increases of 1.7-to 50-fold the original activity of CP (Cheng, Ramakrishnan & Chan, 1999;Kishimura, Hayashi & Ando, 2006) and of APE enzymes (Bolumar, Sanz, Aristoy, & Toldrá, 2003;Dong et al, 2005), activated by cobalt, were attained using 4 µM to 1 mM CoCl 2 . Nevertheless, inhibition of APE by Co 2+ at 10 mM has also been detected (MercadoFlores et al, 2004;Mohamed et al, 2009).…”
Section: Metal Saltmentioning
confidence: 99%
“…Studies on starfish proteases were initiated by Camacho et al (1970) who reported that the purified trypsin-like proteases from the pyloric caeca of the starfish Dermasterias imbricata were capable of hydrolyzing fibrin under alkaline conditions. Kishimura and Hayashi (2002a) and Kishimura et al (2006a) isolated the trypsin from the pyloric caeca of the starfish Asterina pectinifera and carboxypeptidase B from A. amurensis (Kishimura and Hayashi 2002b) and subsequently examined the characteristics and N-terminal amino acid sequences of the two enzymes. The proteases from the digestive tract of the sea cucumber Stichopus japonicus have been purified and characterized as alkaline proteases with optimal activities at pH 8.0 and 13.5.…”
Section: Introductionmentioning
confidence: 99%